The 8th Burnaby Biennial open juried show of edition art. - Burnaby Art Gallery, Burnaby; Summerskill, Paul W. (Burnaby : Burnaby Art Gallery, 1975)
Rawlyk, Mary E. ; Blackwood, David ; III, Charles March ; Maki, Sheila ; McKinnon, Les ; Onley, Toni ; Schmidt, Marianna ; Tetrault, Pierre Leon ; Wherry, Margaret ; Bailey, Diana ; Bettinville, Henri ; Beveridge, Karl ; Bollerup, Ross ; Cain, Wendy ; Caiserman-Roth, Ghitta ; Caron, Quentin ; Chisalita, Cloe ; Cinnamon, Shelley ; Colton, Mamie ; Cookson, Jocelyn B. ; Cragg, Heather D. ; Crammond, Elizabeth ; Daglish, Peter ; Dart, George ; Diakow, Prim-Rose ; Duff, Ann MacIntosh ; Estcott, R.W. ; Esler, John K. ; Fortier, Liliane ; Fortier, Michel ; Fullerton, Ted ; Gagnon, Liz ; Geden, Dennis ; Golden, Lin ; Graham, Robert W. ; Harder, Rolf ; Harris, Lawren P. ; Hastenteufel, Dieter ; Helfield, Tilya ; Hess, Paul ; Hirohata, Seigo ; Hofstetter, John ; Howlin, John ; Hudson, Michael ; Jorgensen, Flemming ; Kakegamic, Goyce ; Kowalsky, Elaine ; Lapointe, Frank ; Lavoy, Ewa Anisimowicz ; MacGregor, John ; Marois, Laureat ; Merkur, Sharon ; Milburn, Marilyn ; Morrison, Hugh ; Myers, Edna ; Ohm, Cecilia M.A. ; O'Keefe, Judith ; Onley, Toni ; Osborne, Lyndal ; Porter, Edward ; Prinsen, Neil ; Rusk, Sue ; Rutherford, Robert ; Savage, Roger ; Sawai, Noboru ; Schwarz, Judith ; Shapiro, Catherine Calkin ; Shepherd, Reginald ; Skalnik, Pavel ; Smutylo, allen ; Spitznagel, Douglas ; Swartzman, Roslyn ; Tétreault, Pierre-Léon ; Weeks, Stephen ; Weinstein, A. ; Wherry, Margaret ; Wright, Douglas ; Yates, Richard ; Zurosky, Louise
Engels
The 8th Burnaby Biennial open juried show of edition art, Burnaby Art Gallery, Burnaby, October 8 - November 9, 1975
boek